2000
DOI: 10.1007/s002030000225
|View full text |Cite
|
Sign up to set email alerts
|

A stable archaeal pyruvate carboxylase from the hyperthermophile Methanococcus jannaschii

Abstract: The pyruvate carboxylase (PYC) of the hyperthermophilic, strictly hydrogenotrophic, autotrophic and marine methanarchaeon Methanococcus jannaschii was purified to homogeneity. Optimal activity was at pH 8.5, > or = 80 degrees C, and a KCl concentration of 0.175 M. This enzyme is the most thermophilic PYC so far studied. Unlike the Methanobacterium thermoautotrophicum enzyme, Mc. jannaschii PYC was expressed in cells grown without an external source of biotin and in the purified form was stable during storage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…The identity of a polypeptide in a gel band was determined by in-gel trypsin digestion, MALDI-TOF 2 mass spectrometry, and data base searches as described previously (13,14). Protein was assayed according to Bradford (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identity of a polypeptide in a gel band was determined by in-gel trypsin digestion, MALDI-TOF 2 mass spectrometry, and data base searches as described previously (13,14). Protein was assayed according to Bradford (15).…”
Section: Methodsmentioning
confidence: 99%
“…2C). Mass spectrometric analyses (13,14) showed that each of these bands corresponded to MJ0870 (data not shown). Therefore, we concluded that the 70-kDa band in Fig.…”
Section: Growth Of M Jannaschii With Sulfite As the Sulfur Source Anmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, OAA synthesis is a central anabolic process in methanarchaea. Thus far, pyruvate carboxylase (PYC) (39,41,42,50) and phosphoenolpyruvate carboxylase (PPC) (14,31,47,60) have been found to be capable of fulfilling this requirement, as follows:PYC is ubiquitous in the methanogens (39,41,42,50), and the primary structure, kinetic characteristics, and expression patterns of the methanogen PYCs have been investigated (39,41,42,50). Methanothermobacter thermautotrophicus (formerly known as Methanobacterium thermoautotrophicum strain ⌬H) (2, 57, 61) and Methanothermus sociabilis also possess phosphoenolpyruvate carboxylase (14,31,47,60), but very little of such information is available on these enzymes.…”
mentioning
confidence: 99%
“…Hence, OAA synthesis is a central anabolic process in methanarchaea. Thus far, pyruvate carboxylase (PYC) (39,41,42,50) and phosphoenolpyruvate carboxylase (PPC) (14,31,47,60) have been found to be capable of fulfilling this requirement, as follows:…”
mentioning
confidence: 99%